2012
DOI: 10.1037/a0026695
|View full text |Cite
|
Sign up to set email alerts
|

Improving access and reducing barriers to depression treatment for Latino elders: Un Nuevo Amanecer (A New Dawn).

Abstract: Cultural adaptations to evidenced-based practices have the potential to bridge scientifically rigorous interventions to underserved populations. Un Nuevo Amanecer (A New Dawn) is a depression treatment program for Latino older adults and elders (age 60 years and older) with depressive disorders (i.e., major depression, minor depression, and dysthymia). We have implemented an evidence-based practice, originally designed for older adults in a primary care setting, into a community center setting serving Latino e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(30 citation statements)
references
References 60 publications
0
29
1
Order By: Relevance
“…One study modifying a depression care management intervention to be more culturally appropriate for Hispanic elders resulted in over a 50% reduction in depressive symptoms, as measured by the Patient Health Questionnaire (PHQ-9), and boasted a retention rate of almost 97% (Chavez-Korell et al, 2012). Further, 98% of participants indicated that they found the services helpful and that they would recommend the services to a friend or family member (Chavez-Korell et al, 2012).…”
Section: Practice Implicationsmentioning
confidence: 96%
See 1 more Smart Citation
“…One study modifying a depression care management intervention to be more culturally appropriate for Hispanic elders resulted in over a 50% reduction in depressive symptoms, as measured by the Patient Health Questionnaire (PHQ-9), and boasted a retention rate of almost 97% (Chavez-Korell et al, 2012). Further, 98% of participants indicated that they found the services helpful and that they would recommend the services to a friend or family member (Chavez-Korell et al, 2012).…”
Section: Practice Implicationsmentioning
confidence: 96%
“…One study modifying a depression care management intervention to be more culturally appropriate for Hispanic elders resulted in over a 50% reduction in depressive symptoms, as measured by the Patient Health Questionnaire (PHQ-9), and boasted a retention rate of almost 97% (Chavez-Korell et al, 2012). Further, 98% of participants indicated that they found the services helpful and that they would recommend the services to a friend or family member (Chavez-Korell et al, 2012). In that study, the modifications to the Improving Mood -Providing Access to Collaborative Treatment (IMPACT) model included adapting the depression care management intervention to take place in a community center, providing materials and services in Spanish, adapting materials for low literacy and illiterate participants, decreasing the amount of clients for each depression care manager, and providing culturally appropriate activities and adaptations that were sensitive to the beliefs and values of Hispanic elders, including familismo, marianismo, and respect for elders (Chavez-Korell et al, 2012).…”
Section: Practice Implicationsmentioning
confidence: 99%
“…Another innovative community-focused strategy was the use of non-clinical, community spaces to increase the acceptability and accessibility of health interventions for the target groups. Community spaces included local churches ( 25 , 31 ) or other religious facilities ( 24 ), a community center ( 32 ), and a community health center ( 33 ) and tribal clinic ( 34 ).…”
Section: Cultural Competency Intervention Strategiesmentioning
confidence: 99%
“…Chavez-Korell et al ( 32 ) reported on a culturally adapted depression treatment for older Latino adults delivered through a community center located in an area with a high older Spanish-speaking, low-acculturated, and first-generation immigrant population. The target population had a strong sense of trust and identification with the center, and already attended regularly for a variety of services and programs.…”
Section: Cultural Competency Intervention Strategiesmentioning
confidence: 99%
“…The literature on the effectiveness of various psychological treatment modalities for ethnic minority groups-as well as the risk factors associated with anxiety and depression, specifically among elders of Mexican origin (Chavez-Korell et al, 2012;Vink, Aartsen, & Schoevers, 2008)-is limited. While the need is significant; too few mental health professionals from ethnic and non-ethnic minority groups are interested in geropsychology (Karel et al, 2012).…”
Section: Introductionmentioning
confidence: 99%